Edukasi Remaja Dalam Menghadapi Masa Pubertas di SMP Negeri 14 Kendari - Sartiah Yusran; I Putu Sudayasa; Aisyah Amini; Ardiansyah Mahlia; Asdwiyenti Miftahulresty Aksi; Ashar; Ayuningtyas Mardhatillah; Diva Janianti; Hasnianti (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
Adolescence is a transitional period marked by various physical and psychological changes. The increasing curiosity of adolescents regarding the changes occurring in their bodies encourages them to seek information about these changes. However, this condition may influence attitudes and lead to risky behaviors if adolescents receive inaccurate information about reproductive health. The purpose of this activity was to improve the knowledge, understanding, and positive attitudes of students at Junior High School 14 Kendari in facing puberty. The target of the counseling activity was students of Junior High School 14 Kendari, consisting of a combined group from grades VII, VIII, and IX, with a total of 40 students representing each class, where two students were selected from each class. The methods used in this health education activity included educational video screening, interactive presentations, discussions, and question and answer sessions. The evaluation was conducted qualitatively through observation and student responses during the activity. The students demonstrated an understanding of the basic concepts of puberty, physical and psychological changes, and the importance of maintaining personal hygiene and health. This was reflected in students’ statements such as “now I know that the changes in my body are normal” and “I am no longer embarrassed to ask questions about puberty.” In addition, increased student participation in discussions indicated improved self-confidence in facing puberty. The conclusion of this activity is that health education can enhance adolescents’ knowledge and self confidence related to puberty